Physical chemistry from a different angle : introducing chemical equilibrium, kinetics and electrochemistry by numerous experiments - Job, Georg; Ruffler, Regina
From back cover: Learning the basics of physical chemistry with a unique, innovative approach. Georg Job and Regina Rueffler introduce readers to an almost intuitive understanding of the two fundamental concepts, chemical potential and entropy. Avoiding complex mathematics, these concepts are illustrated with the help of numerous demonstration experiments. Using these concepts, the subjects of chemical equilibria, kinetics and electrochemistry are presented at an undergraduate level. The basic quantities and equations necessary for the qualitative and quantitative description of chemical transformations are introduced by using everyday experiences and particularly more than one hundred illustrative experiments, many presented online as videos. These are in turn supplemented by nearly 400 figures, and by learning objectives for each chapter. From a review of the German edition: “This book is the most revolutionary textbook on physical chemistry that has been published in the last few d